DETERMINANT OF HEALTH INSURANCE ENROLLMENT FOR THE INFORMAL SECTOR IN LOW AND MIDDLE-INCOME COUNTRIES: A SYSTEMATIC REVIEW (Proceedings of the International Conference on Public Health, 2023)
The health insurance schemes are implemented to achieve universal coverage through covering medical expenses that emerge due to an illness. This study was a systematic review to identify and analyze factors associated with health insurance enrollment for the informal sector that dominates the workforce in most developing countries. Six databases, namely: PubMed, Taylor and Francis online (Tandfonline), Science Direct, Scopus, Journal Storage (JSTOR) and Google Scholar were systematically traced in September-October 2020 to identify English-language research that analyzed the determinants of health insurance enrollment for the informal sector and published in the period 2010-2020. A total of 15 articles both quantitative and mix-methods analysis were included after final assessment. Most of the studies was conducted in Africa and Asia and only one article was conducted in Latin America. All studies demonstrated several factors associated to health insurance registration including sociodemographic characteristics, knowledge, chronic disease, information, and health service utilization, premium, subsidy, health status, trust, and capital, drug provision, perceived susceptibility, perceive seriousness, perceived benefit, family and social support. Findings from this systematic review can be encourage for policy-makers interested in expansion of health insurance membership for informal workers especially in developing countries.
Keywords: determinant, enrollment, health insurance, informal sector